Association between Doctor’s Motivation, Age, and Leadership on Patient’s Satisfaction: A Path Analysis Evidence - Lukman Aryoseto; Didik Tamtomo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Quality health care needs are increasing. The service quality of one public health center and another does not have the same standard yet. One of the factors that influence the assessment of service quality is patient satisfaction. Several factors can influence patient satisfaction, especially from the doctor's side. This study aims to determine the effect of physician motivation, the age of the doctor, and the head of the health center on physician job satisfaction and patient satisfaction.Method: This was an analytic observational study with a cross-sectional design. The study was conducted at community health centers in Karanganyar and Surakarta, Central Java, in August 2018. A total of 25 doctors and 225 patients were selected using proportional random sampling. The dependent variable in this study is patient satisfaction. The independent variables in this study were the doctor's motivation, doctor's work satisfaction, doctor’s age, and the head of the health center. Data were obtained using questionnaires and analyzed using path analysis.Results: Patient satisfaction was directly increased by by the doctor's work satisfaction (b = 0.10; SE= 0.02; p<0.001) but decreased by doctor’s age (b= -0.82; SE= 0.02; p<0.001). Patient satisfaction was indirectly affected by doctors' motivation and head of community health center.Conclusions: Patient satisfaction is directly increased by the doctor's work satisfaction but decreases by doctor’s age. Patient satisfaction is indirectly affected by doctors' motivation and head of community health center.Keywords: patient satisfaction, doctor’s motivation, leadership, community health centerCorrespondence: Lukman Aryoseto. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: lukmanaryoseto@gmail.com.Journal of Health Policy and Management 4(1): 31-38https://doi.org/10.26911/thejhpm.2019.04.01.04